2007
DOI: 10.1590/s0034-89102006005000022
|View full text |Cite
|
Sign up to set email alerts
|

Álcool e adolescentes: estudo para implementar políticas municipais

Abstract: OBJECTIVE:To build students' profi le regarding alcohol consumption and risk behavior. METHODS:A total of 1,990 students were included in the study, aged 11 to 21 years old, from both genders, enrolled in public and private schools, in Southeastern Brazil, in 2004. A self-administered questionnaire was answered in the classroom without the presence of the teacher. The questionnaire also assessed the perception of how easy it was to get alcoholic beverages, the contexts where they drunk, and the consequences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
67

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 14 publications
0
24
1
67
Order By: Relevance
“…The literature defines as an excessive intake of alcohol the consumption of ≥ 14 doses/week. 23,24 Body mass and height were self-reported. The validity of these measures has been demonstrated in the Brazilian adult population.…”
Section: Independent Variablesmentioning
confidence: 99%
“…The literature defines as an excessive intake of alcohol the consumption of ≥ 14 doses/week. 23,24 Body mass and height were self-reported. The validity of these measures has been demonstrated in the Brazilian adult population.…”
Section: Independent Variablesmentioning
confidence: 99%
“…In Brazil, alcohol is also the most widely used drug in any age group and an increased consumption among adolescents can be verified (13) . Furthermore, this same study has demonstrated a high consumption of alcohol and tobacco among students as it was also observed in our study, suggesting that adolescents can easily buy alcohol or cigarettes, either via market places as through their social and family groups ( relatives and friends).…”
Section: Discussionmentioning
confidence: 99%
“…[13]. Moreover, these adolescents were found to have easy access to alcohol despite the prohibition for minors: adolescents under the minimum legal age were successful in purchasing alcoholic beverages at the first attempt in 85.2% of the surveyed outlets in Paulinia and 82.4% in Diadema [14,15].…”
Section: Community Interventionsmentioning
confidence: 99%